Hakikat Manusia dan Relevansinya dengan Pendidikan di Era Society 5.0 - Nurdiyanto, Nurdiyanto; Islam, Muhammad Thoriqul; Al Baqi , Safiruddin; Novitasari, Dwiana; Azmi, M. Ulul (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
Humans are endowed with reason, desire, and intellect. To cultivate humanity and guide human behavior, education serves as an essential reference and framework. Through education, life will be more focused on the goals it achieves. The research aims to comprehensively describe the understanding of humans and its relevance to education as the primary means for humans. This article results from literature (library) and analytical description using existing evidence. The research method used is library research to solve a problem. This research was conducted by reviewing the literature data in depth, both secondary and primary. From the results of this study, the author found that humans will not be separated from the corridor that has been determined by the code of ethics in education based on the Qur'an and As-Sunnah, Ijma and Qiyas, with their respective paths and in the end humans will always obey and obey the commands of the Creator as the God of the universe so that the meaning of Humans and their Relevance to Education is to create people who have good character and have knowledge that is balanced with the development of the era.